Size, Aspect Ratio and Anatomic Location of Ruptured Intracranial Aneurysms: Consecutive Series of 415 Patients from a Prospective, Multicenter, Observational Study. Issue 6 (June 2019) - Zheng, Y.; Zhou, B.; Wang, X.; Chen, H.; Fang, X.; Jiang, P.; Yang, H.; He, C.; Yang, G.; Song, Y.; An, Q.; Leng, B.
To analyze the size and location distribution of ruptured intracranial aneurysms (IAs) helps to provide evidence for clinical treatment of unruptured IAs using this feature of aneurysms. In this study, 415 patients who presented with an acute subarachnoid hemorrhage caused by IAs were enrolled from eight tertiary referral centers between June 2016 and March 2018. The size, aspect ratio and anatomic location of ruptured IAs were defined and reported by patient sex. In the study cohort of 415 patients (60.5% women) with saccular ruptured IAs, the three most common locations of ruptured IAs were posterior communicating artery (32.0%), anterior communicating artery (28.7%), and middle cerebral artery (13.5%). The mean size of all ruptured IAs was 5.3±3.1 mm (range 1.1–28.5 mm), but the size varied considerably by location. For example, ruptured IAs of the posterior communicating artery had a mean size of 5.8±3.1 mm, whereas the mean size of ruptured anterior communicating artery aneurysms was 4.6±1.7 mm. The mean AR in all ruptured IAs was 1.66±0.76. Of those aneurysms, 243 (58.6%) had an AR smaller than 1.6 and 318 (76.6%) had an AR smaller than 2.0. Our results suggested that the size of the most ruptured IAs are smaller than 7 mm or even 5 mm. The size and AR varied by sex and location. With the knowledge of size, location and AR, multiplicity should be considered for treatment strategies of unruptured IAs.